Titanium implant osseointegration in rheumatoid arthritis patients: Two case reports - Shokri, Mehran; Rostamiana, Jafar; Chegini, Zahra (Journal of Dental School, 2019)
Case Implant rehabilitation in patients suffering from rheumatoid arthritis (RA) has been reported an improvement in the quality of life. Implanttreatment success depends on many factors like achievement of appropriate osseointegration. There are many controversies about theinteractions between anti-rheumatic drugs and osseointegration. Moreover, the scientific evidence regarding implant survival in RApatients are scarce. This study presents two case reports including 65- and 51-year-old women who have used low-dose methotrexate andother anti-rheumatic drugs treated by dental implants. After 4-years follow-up, the patients are satisfied of function and aesthetics. Stablebone level was seen around all implants radiographically. Because of the lack of agreement in implant treatment protocol in RA patient,more studies are suggested.